A casa de Porto Seguro : estudo da morfologia da casa portuguesa no Brasil - Ramalho, Lucemar Franco (2014)
The study of the morphology of Dr. Antonio Ricaldi Street homes in Upper city of Porto Seguro in the state of Bahia aims to clarify the limits of the influence of Portuguese architecture in constructing houses of the historic site that listed by IPHAN sin